Literasi Media Digital dalam Dakwah Islam - Fatimah Azzahro; Julia Fasha (ANWARUL, 2025)
The transformation of information technology has shifted the paradigm of Islamic dakwah from conventional methods to a participatory and interactive two-way communication model through various digital platforms. This study aims to construct the relationship between Islamic dakwah methods and digital media literacy within the context of modern religious education and communication. A literature review method was employed by examining scholarly works related to dakwah strategies, digital media, and media literacy. The findings reveal that digital dakwah is not merely an adaptation to technological advancements but also represents an epistemological transformation that demands creativity, wisdom, and an understanding of the socio-cultural context of digital society. Digital media literacy plays a crucial role in maintaining the integrity of dakwah, safeguarding it from value distortion, misinformation, and hate speech. Digital literacy competencies for da’i include the ability to access, evaluate, and ethically produce content, aligning with the principles of al-hikmah, al-mau‘izhah al-hasanah, and al-jidal bi al-lati hiya ahsan. Thus, digital literacy functions not only as a technical skill but also as a form of bashirah—dakwah grounded in knowledge, strategic awareness, and spiritual consciousness. The main conclusion of this study is that integrating digital literacy into dakwah practices can foster an intelligent, moderate, and humanistic Islamic dakwah ecosystem. Practically, this highlights the importance of creatively packaged dakwah that resonates with the digital generation's lifestyle, while socially, media literacy becomes a strategic instrument in combating disinformation and strengthening ukhuwah and humanitarian values. These findings also expand the dimension of digital literacy as an integral part of spirituality and intellectualism in contemporary dakwah practice.